Effect of decitabine on PD-L2 methylation in whole blood of iodine-induced autoimmune thyroiditis rats - Baiming Jin; Yanbo Qi; Hong Chao; Xiaolei Yang; Hongjie Li; Siyuan Wan (Ecotoxicology and Environmental Safety)
Excessive iodine intake can induce autoimmune thyroiditis (AIT), and the methylation of programmed death receptor 2 (PD-L2) may be involved in the development of iodine-induced AIT. Here, we investigated the immune role of methylation of the susceptibility gene PD-L2 in the occurrence of iodine-induced AIT using the DNA methyltransferase inhibitor Decitabine (Dec) in an experimental autoimmune thyroiditis (EAT) rat model. After injecting Dec intraperitoneally into EAT rats, we performed arsenic-cerium catalytic spectrophotometry, pathological hematoxylin and eosin staining, enzyme-linked immunosorbent assay, quantitative methylation-specific polymerase chain reaction (qMSP), and quantitative real-time polymerase chain reaction (qPCR) to determine the relevant indices. The results showed that compared with the control group, the urinary iodine, thyroid lymphocyte infiltration, thyroglobulin antibody (TgAb), interferon (IFN-γ), and interleukin (IL-23) levels of the EAT rats were significantly increased. The PD-L2 methylation levels were significantly decreased in EAT rats compared to control rats, and the mRNA expression of the PD-L2 was significantly increased. Following Dec intervention, the methylation level of the PD-L2 in rats increased and interferon and interleukin-23 levels decreased, albeit not significantly. However, the mRNA expression of PD-L2 decreased significantly after Dec intervention, and the thyroid function of EAT rats also showed a gradual improvement trend. In summary, hypomethylation of PD-L2 is closely related to the development of iodine-induced AIT. Pro-inflammatory cellular factors are also involved in iodine-induced AIT progression. Although Dec shows promise in the treatment of AIT, further evaluation of its safety is necessary.